Substrate-constrained deformation in thin metal films: numerical case studies. (9th January 2009) - Shen, Yu-Lin
Numerical analyses of deformation in thin metal films are presented, with a focus on the effect of physical constraint imposed by the underlying substrate material. Continuum-based finite element modelling is used, for the purpose of establishing an overall mechanistic view without recourse to microstructural details. The model systems consist of aluminium in the thin-film form, with possible silicon, polyimide or silicon dioxide directly bonded to the metal. Particular attention is devoted to correlating the overall material response with the evolution of local stress and deformation fields. We highlight certain unique features to help facilitate a better understanding of the deformation characteristics and clarify some common misconceptions.